PERANAN KOMITMEN PROFESI AKUNTAN DALAM MEMODERASI PENGARUH CLIENT IMPORTANCE PADA KUALITAS AUDIT - Sunitha Devi; Luh Gede Kusuma Dewi; Putu Eka Dianita Marvilianti Dewi (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2019)
This research was done in purpose of finding out empirical evidences about theeffects of client importance towards the audit quality, dan the commitment ability of the accounting profession in weakening the influence of client importance on audit quality. The research sample that returned the results of questionnaires is 36 auditors from a total of 65 auditors working in the Public Accounting Firm (KAP) in 2018. The sample selection was done using the purposive sampling method. The data sources used in this study are primary data. Primary data is obtained by using a questionnaire that has been structured in order to collect information from the auditor as the respondent in this study. MRA model analysis was applied to analyze the data. The data analysis support the hypothesis: (1) client importance has negative dan significant effect towards the audit quality, dan (2) commitment of the accounting profession was able to moderate the influence of client importance on audit quality. The results of this study can be used as reference material for KAP leaders in evaluating dan performing more strict supervision on the implementation of professional commitment of auditors when conducting audit process, because the existence of KAP depends on the quality of audits that can affect public trust. Regulators can also make very strict rules dan sanctions related to violations of the accounting code of ethics dan violations of the audit process so that they can cause deterrent effects for the perpetrators dan can be used as learning for other auditors so as not to violate these rules.